The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21649/akemu.v22i1.793
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Treatment with Titanium Elastic Nail Versus AO – Dynamic Compression Plate for Femoral Shaft Fractures in Children

Abstract: <p><strong>Abstract</strong></p><p><strong>Background:  </strong>Femur fractures are among the commonest pediatric injuries. Until recent past, traction and hip spica were the standard treatment for all femoral shaft fractures which required long duration of hospitalization. The management of femoral shaft fractures in children above the age of six years has evolved more towards operative approaches in the last two decades to minimize the post plaster complications i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thirteen studies (11 retrospective cohorts; 2 prospective randomized controlled trials) reporting 805 closed femoral fractures in 801 children were eligible for inclusion (Table 1). 1,[16][17][18][19][20][21][22][23][24][25][26][27] Studies were from the United Kingdom, United States, Israel, India, China, and Pakistan. There were 559 males (69.8%) and 242 females (30.2%) with the reported mean ages in the included studies ranging from 5.9 to 10.6 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies (11 retrospective cohorts; 2 prospective randomized controlled trials) reporting 805 closed femoral fractures in 801 children were eligible for inclusion (Table 1). 1,[16][17][18][19][20][21][22][23][24][25][26][27] Studies were from the United Kingdom, United States, Israel, India, China, and Pakistan. There were 559 males (69.8%) and 242 females (30.2%) with the reported mean ages in the included studies ranging from 5.9 to 10.6 years.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the secondary outcomes, infection (of the bone or the soft tissues) was reported in all studies (Table 3). 1,[16][17][18][19][20][21][22][23][24][25][26][27] Twelve studies 1,16,[18][19][20][21][22][23][24][25][26][27] reported leg-length difference and 11 studies [16][17][18][19][20][21][22][23][24][25][26][27] reported unplanned reoperations (Table 4). These secondary outcomes were pooled and are expressed as summary statistics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation